Speech intelligibility of children with an auditory brainstem implant: a triple-case study. (2nd December 2022) - Faes, Jolien; De Maeyer, Sven; Gillis, Steven
ABSTRACT: Auditory brainstem implantation (ABI) is a relative recent development in paediatric hearing restoration. Consequently, young-implanted children's productive language has not received much attention. This study investigated speech intelligibility of children with ABI (N = 3) in comparison to children with cochlear implants (CI) and children with typical hearing (TH). Spontaneous speech samples were recorded from children representing the three groups matched on cumulative vocabulary level. Untrained listeners (N = 101) rated the intelligibility of one-word utterances on a continuous scale and transcribed each utterance. The rating task yielded a numerical score between 0 and 100, and similarities and differences between the listeners' transcriptions were captured by a relative entropy score. The speech intelligibility of children with CI and children with TH was similar. Speech intelligibility of children with ABI was well below that of the children with CI and TH. But whereas one child with ABI's intelligibility approached that of the control groups with increasing lexicon size, the intelligibility of the two other children with ABI did not develop in a similar direction. Overall, speech intelligibility was only moderate in the three groups of children, with quite low ratings and considerable differences in the listeners' transcriptions, resulting in high relative entropy scores.